THE USAGE OF CRITICAL THINKING TECHNOLOGY IN ENGLISH LESSONS - Rakhimdjanova Malikakhon (Researchparks Publishing, 2022)
The article describes issues based on the essence of using critical thinking technology during the lessons. It is known that gaining any knowledge will be better if it is based on one's own experience. Bringing to the surface representations or more stable forms of student knowledge on the topic studied is not an easy task, but it will greatly simplify the path to new knowledge for the students. The most difficult thing for a teacher is to accept all the versions that students offer - right and wrong. It is better to fix them in writing. Sometimes contradictions in points of view are revealed. When contradictions are visible or it is clear that the information collected is not enough, the guys have a desire to overcome this. In essence, they form a goal for themselves: why will I study new material, what exactly do we need to know in order to answer own question.